Competency need assessment for academic teaching librarians in higher learning institutions/ Mohd Razif Dzulkipli, Roziya Abu and Norshila Shaifuddin - Dzulkipli, Mohd Razif; Abu, Roziya; Shaifuddin, Norshila (Faculty of Information Management, 2025)
Academic librarian works in academic library and perform task of developing information literacy and teaches in classes to educate higher learning institution’s stakeholder. The article is to assess the need of competency index for teaching librarian especially in academic libraries. This need assessment is a descriptive and exploratory research, was conducted to Chief Librarians and teaching librarians who serves public academic libraries. The objective of this analysis is to identify whether teaching librarian needs specific competencies to validate their practice of pedagogy in academic libraries. A preliminary study through descriptive research which involved sample size of 20 prominent library administrators and 20 teaching librarians from public universities in higher education. A set of 7-10 questions was sent through email to all public academic library’s Chief Librarians and teaching librarian. 95% of them responded to the questionnaire. The result shows that, 85% of the Chief Librarians agrees that teaching librarian need specific range of competence index so they can successfully perform the pedagogy practice.